Legal Protection of Persons with Mental Disabilities in Managing Inheritance Case Study of Dalu Village 10A - Ramadhani, Tasyah Ramadhani; Irwan, Irwan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
This research aims to analyze the legal protection for people with mental disabilities in managing inheritance, focusing on a case study in Dalu 10A Village. From the perspective of Islamic law and the Civil Code, this research explores how their civil rights are protected. The research method used is a type of empirical legal research in qualitative research. The results show that although Law No. 19/2011 states that people with disabilities should be treated equally with the rest of society, in practice, people with mental disabilities are often denied their rights in inheriting property and face a lack of legal protection. This research highlights a case example in Dalu 10A Village, where the distribution of inherited property was not in accordance with existing provisions, demonstrating the need for improved understanding and implementation of disability rights protected by law. The research found that people with mental disabilities are categorized as legally incapable and unable to act in their personal interests, making the appointment of a guardian essential to preserve their rights. The application to become a guardian is submitted to the district court or religious court, in accordance with the regulations contained in Article 1 of Law No. 8/2016 and the Civil Code. This research provides insight into the challenges faced by people with mental disabilities in the context of estate management and emphasizes the importance of adequate legal protection to ensure their rights are respected and maintained.